The Study of Tourism’s Infrastructure Investment in Gangga Island Likupang Country - Sasela, Notje (JBE (Journal of Business and Economics); Volume 4 No.2, 2005 JBE UNKLAB, 2005)
This study aim to look into the investment of tourism’s onfrastructure in Gangga Island and to identify the investment and marketing facrots such as: transportations, accommodations, communications, information technology, security, objects of tourism, advertising, and environment. This research study examined the effect to investment and marketing factors of tourism’s infrastructure to marketing productivity. This research study used descriptive method to survey the perceptions od the people in Gangga Island. The data was gathered from the people by using purposive and judgment sampling. Questionnaire and interview were the instruments used to collect th primary data. A Likert Scale was used to measure the eight factors of invesment and marketing of tourism’s infrastructurre: transportation, accommodation, communication, information technology, security, tourism’s objects and activities, promotion/advertising, and environment. After the data colled by interview and observation, then it was analyzed by using multiple regression and correlation. The results was in the aggregate, all the factors of investment and marketing, that consist of transportations, accommodations, communication, information technology, security, tourism’s objects and activities, promotion/advertising, and environment were effect to the marketing productivity, and in the partials as well. From this research it can be concluded that the marketing productivity was determined by the elements of investment and marketing factors such as: transportation, accommodation, communication, information technology, security, objects of tourism, advertising, and environment in the aggregate were effect the marketing productivity.